Th17 Cell Accumulation Is Decreased during Chronic Experimental Colitis by (n-3) PUFA in Fat-1 Mice(2) - Monk, Jennifer M. (American Society for Nutrition, 2012)
During colon inflammation, Th17 cells and immunosuppressive regulatory T cells (Treg) are thought to play promotive and preventative roles, respectively. Dietary (n-3) PUFA favorably modulate intestinal inflammation in part by downregulating T-cell activation and functionality. We used the Fat-1 mouse, a genetic model that synthesizes long-chain (n-3) PUFA de novo, to test the hypothesis that (n-3) PUFA protect against colonic inflammation by modulating the polarization of Treg and Th17 cells during colitis. Male and female wild-type (WT) and Fat-1 mice were administered dextran sodium sulfate (DSS) in the drinking water (2.5%) to induce acute (5 d DSS) or chronic (3 cycles DSS) colitis and the percentage of Treg and Th17 cells residing locally [colonic lamina propria (cLP)] and systemically (spleen) was determined by flow cytometry. The percentage of Treg in either tissue site was unaffected by genotype (P > 0.05); however, during chronic colitis, the percentage of Th17 cells residing in both the spleen and cLP was lower in Fat-1 mice compared to WT mice (P < 0.05). Colonic mucosal mRNA expression of critical Th17 cell cytokines and chemokine receptors (IL-17F, IL-21, and CCR6) were lower, whereas expression of the Th17 cell suppressive cytokine, IL-27, was greater in Fat-1 mice compared to WT mice during chronic colitis (P < 0.05). Moreover, colon histological scores were improved in Fat-1 mice (P < 0.05). Collectively, these results demonstrate for the first time, to our knowledge, that (n-3) PUFA can modulate the colonic mucosal microenvironment to suppress Th17 cell accumulation and inflammatory damage following the induction of chronic colitis.